The ecology of southern African wild silk moths (Gonometa species, Lepidoptera: Lasiocampidae): consequences for their sustainable use - Scholtz, Clarke H. (University of Pretoria, 2013)
Thesis (DPhil (Entomology))--University of Pretoria, 2007.